2022
DOI: 10.1038/s43246-022-00302-x
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-solid contact electrification when water droplets hit living plant leaves

Abstract: Contact electrification has gained interest as a mechanism for generating charges on surfaces. It has also been shown that plant leaves generate electrification by both solid-solid and liquid-solid contact. However, it is unclear how water droplets hitting a leaf causes charging and which structural features affect this phenomenon. Here, we show how the in-situ surface structures of leaves, droplet composition, and prior ionization of the droplet influence living plant liquid-solid contact electrification on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Observations of Jie et al 119 , Feng et al 120 and Ding et al 121 suggest that this results from their ability to act as triboelectric nanogenerators when they harvest mechanical energy from low-frequency motion to generate long- or short-lived static surface charge. This generation of positive triboelectric charge 122 , 123 appears to be species-specific. Second, agates and marble are exceptional among stones.…”
Section: Discussionmentioning
confidence: 92%
“…Observations of Jie et al 119 , Feng et al 120 and Ding et al 121 suggest that this results from their ability to act as triboelectric nanogenerators when they harvest mechanical energy from low-frequency motion to generate long- or short-lived static surface charge. This generation of positive triboelectric charge 122 , 123 appears to be species-specific. Second, agates and marble are exceptional among stones.…”
Section: Discussionmentioning
confidence: 92%
“…Water drops sliding down on plant leaves or hydrophobic surfaces get electrically charged. [1][2][3][4] This phenomena is known as slide electrification. Understanding and controlling drop sliding behavior is the key knowledge in dropwise condensation, 5 inkjet printing, 6 water desalination, 7 and drop manipulation in microfluidic devices.…”
Section: Introductionmentioning
confidence: 99%
“…They investigated the power generation phenomenon and working mechanism of a triboelectric nanogenerator under diverse droplet compositions, different external resistive loads, and different droplet impact locations in contact conditions. Armiento et al [13] conducted an experimental comparison of droplet impacts on leaves with waxy layers under three conditions: retaining the wax layer, melting the wax layer, and removing the wax layer. The results indicated that the removal of leaf epicuticular waxes negatively affected the signal generation of droplet impacts on plant leaves.…”
Section: Introductionmentioning
confidence: 99%